Studi Farmakologi Ikan Zebra sebagai Model Obesitas dan Hiperglikemia: Pengembangan Induksi Diet-Induced Obesity - Nurfakhrurajab, Irfan; Elfita, Lina; Fitriana, Narti (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Obesity and hyperglycemia are major risk factors for type 2 diabetes mellitus and various other metabolic disorders. The use of relevant animal models is essential to support pharmacological studies. The aim of this research was to develop an effective DIO (Diet-Induced Obesity) inducer for commercially available zebrafish as a model for obesity and hyperglycemia. Adult zebrafish were induced for obesity and hyperglycemia through administration of a high-fat diet for 4 weeks. The observed parameters included body weight, body length, body mass index (BMI), and blood glucose levels. The results showed that DIO induction significantly increased body weight, BMI, and blood glucose levels (P < 0.05) compared to the control group. In conclusion, zebrafish can be developed as a model for obesity and hyperglycemia through DIO induction, thus potentially serving as an alternative test animal for pharmacological studies of metabolic diseases.